Practice of New Normal Lifestyles, Economic and Social Disruption, and Level of Happiness Among General Public in China in the Post-COVID-19 Era - Lin X; Lin Y; Hu Z; Alias H; Wong LP (Dove Medical Press, 2021)
Xu Lin,1 Yulan Lin,2 Zhijian Hu,2 Haridah Alias,3 Li Ping Wong2,3 1Department of Respiratory and Critical Care Medicine, Fuzhou Pulmonary Hospital of Fujian, Educational Hospital of Fujian Medical University, Fuzhou, 350004, Fujian, People’s Republic of China; 2Department of Epidemiology and Health Statistics, School of Public Health, Fujian Medical University, Fuzhou, 350122, Fujian, People’s Republic of China; 3Centre for Epidemiology and Evidence-Based Practice, Department of Social and Preventive Medicine, Faculty of Medicine, University of Malaya, Kuala Lumpur, 50603, MalaysiaCorrespondence: Yulan Lin Email yulanlin@fjmu.edu.cnLi Ping Wong Email wonglp@ummc.edu.myPurpose: This study aimed to investigate the impact of the COVID-19 pandemic on the practice of ‘new normal’ lifestyles, economic and social distribution, and individuals’ well-being of people in China after the country ease the lockdown restriction.Methods: A cross-sectional, self-administered online survey was carried out between 3 September and 15 October 2020.Results: A total of 8393 complete responses were received from a nationwide sample. Poor sustainability in the practice of “new norm” was reported. Noteworthy disparities were observed in willingness to carry out “new normal” practices by gender, urban-rural locality, non-Han and Han Chinese and educational attainment. There was evidence of economic and social disruption associated with COVID-19 or “new normal” practices. The current mean (±standard deviation [SD]) happiness score (110.45 ± 17.55) was slightly lower than the mean happiness score before (111.12 ± 17.83) the COVID-19 pandemic (t= − 9.01, p< 0.001). Lower socioeconomic status and greater economic and social disruptions were associated with lower current happiness scores. Moreover, greater willingness to adapt to “new normal” practices was associated with higher levels of happiness.Conclusion: There is a need to encourage sustainable practice of new norm post-pandemic. Segments of the public continue to experience significant economic and social effects and the post-pandemic ‘new norms’ remain at risk of leading to psychological consequences.Keywords: new-normal, COVID-19, happiness index